Reefs shift from net accretion to net erosion along a natural environmental gradient - Nyssa J. Silbiger; Oscar Guadayol roig; Florence I. M. Thomas; Megan J. Donahue (2014)
Coral reefs persist in an accretion-erosion balance and ocean acidification resulting from anthropogenic CO2 emissions threatens to shift this balance in favor of net reef erosion. Corals and calcifying algae, largely responsible for reef accretion, are vulnerable to environmental changes associated with ocean acidification, but the direct effects of lower pH on reef erosion has received less attention, particularly in the context of known drivers of bioerosion and natural variability. This study examines the balance between reef accretion and erosion along a well-characterized natural environmental gradient in Kane'ohe Bay, Hawai'i using experimental blocks of coral skeleton. Comparing before and after micro-computed tomography (mu CT) scans to quantify net accretion and erosion, we show that, at the small spatial scale of this study (tens of meters), pH was a better predictor of the accretion-erosion balance than environmental drivers suggested by prior studies, including resource availability, temperature, distance from shore, or depth. In addition, this study highlights the fine-scale variation of pH in coastal systems and the importance of micro habitat variation for reef accretion and erosion processes. We demonstrate significant changes in both the mean and variance of pH on the order of meters, providing a local perspective on global increases in pCO(2). Our findings suggest that increases in reef erosion, combined with expected decreases in calcification, will accelerate the shift of coral reefs to an erosion-dominated system in a high-CO2 world. This shift will make reefs increasingly susceptible to storm damage and sea-level rise, threatening the maintenance of the ecosystem services that coral reefs provide.